Transverse piezoelectric properties of Mn-doped Bi0.5Na0.5TiO3 thin films - Nguyen, Bich Thuy; Won, Sung Sik; Chan Park, Bong; Jo, Yong Jin; Ahn, Chang Won; Kim, Ill Won; Kim, Tae Heon (Current applied physics, 2020)
Lead-free (Bi0.5Na0.5)(Ti1-xMnx)O3 (BNTMn-x; x = 0, 0.0025, 0.0050, 0.0100) thin films were fabricated using a chemical solution deposition method on Pt/TiO2/SiO2/Si substrate. The effect of Mn substitution on crystal structures, surface morphologies, and ferroelectric and transverse piezoelectric properties of BNTMn-x thin films was investigated. The 0.5 mol% Mn-doped (Bi0.5Na0.5)(Ti0.995Mn0.005)O3 thin film exhibited a well-saturated ferroelectric P-E hysteresis loop at room temperature. A remnant polarization (Pr) of 16 μC/cm2 was obtained for the BNTMn-0.0050 film at an applied electric field of 400 kV/cm. In addition, a 1.12-μm-thick BNTMn-0.0050 film was applied as a cantilever. The Pt/BNTMn-0.0050/Pt/TiO2/SiO2/Si unimorph cantilever exhibited a high transverse piezoelectric coefficient (e31∗) of 2.43 C/m2. [Display omitted]